Do Implementation Of Accounting Learning Multimedia Affect Students’ Soft Skills? - Trisna Herawati, Nyoman; Sinarwati, Ni Kadek (Journal of Education Reseach and Evaluation, 2018)
The objective in this research is to analyze inferential comparative advantages between the use of multimedia and print media to improve student soft skills. The study uses a quasi-experimental with pretest-posttest nonequivalent control group design. The population was students of S1 Accounting Study Program in their second semester who were taking Introductory Accounting courses 2. Sampling was done by simple random sampling. The data collected through observation methods and assignment values. Data were analyzed by descriptive statistical techniques and inferential statistics uses analysis of covariant (ancova) with pretest score as covariables. The results showed, the average of soft skills the experimental group is 24.49, higher than the control group. The results of the ancova test produce a statistical value of F of 5,400 with a significance of 0.023. This shows that after being controlled by the pretest covariables, there are significant differences in soft skills between the experimental groups that conduct learning with multimedia compared to the control group that conducts learning with conventional media (print media). Students who are given learning using multimedia have better soft skills than students who are taught using print media. The amount of adjusted R square value of 0.470 means that the variability of soft skills can be explained by the variability of learning media (multimedia) as much as 47.0%.